Medication Adherence: does Patient Participation in Randomized Clinical Trials Affect on it? - N. O. Vasyukova; Yu. V. Lukina; N. P. Kutishenko; S. Yu. Martsevich; O. I. Zvonareva (Рациональная фармакотерапия в кардиологии)
The article focuses on the problem of low adherence to treatment among patients, in general, and provides data on the high adherence among patients in randomized controlled trials. Low adherence remains one of the most debated and difficult problems to solve nowadays. Poor medication adherence of the patient can significantly worsen the effectiveness of treatment and leads to increased health care costs. And although the factors that improve adherence are varied, and include the skills of the doctor, the patient’s personal characteristics, the external environment, an individual approach to each patient and etc., the absence of a “gold standard” for assessing adherence in clinical practice makes it difficult to predict and significantly improve it among patients. Nevertheless, the article discusses the existing doctor-patient interaction model, which strictly regulates the algorithms and technical means to achieve the best medication adherence. Randomized clinical trials (RCT) are the basis of evidence-based medicine, the results obtained in RCT form the basis of existing clinical guidelines. While participating in RCT patients can receive comprehensive information about the disease, the effectiveness of drug therapy, possible side effects of the therapy being conducted, the research objectives and prognosis from their attending physician; patients are trained to be disciplined and adhere to the recommendations of the doctor. The RCT, for a number of objective reasons, uses a variety of methods for assessing adherence and ways to improve it, which leads to higher patient adherence then among patients in general.